The deduced structure of the T cell receptor gamma locus in Canis lupus familiaris - Massari, S.; Bellahcene, F.; Vaccarelli, G.; Carelli, G.; Mineccia, M.; Lefranc, Mp; Antonacci, R.; Ciccarese, S. (Molecular Immunology, 2009)
International audience